1992
DOI: 10.1002/jbm.820260210
|View full text |Cite
|
Sign up to set email alerts
|

Differences in ceramic–bone interface between surface‐active ceramics and resorbable ceramics: A study by scanning and transmission electron microscopy

Abstract: The interface between bioactive ceramics and bone was studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The materials were apatite-wollastonite-containing glass ceramic (A-W.GC) as a representative surface-active ceramic, and calcite and beta-tricalcium phosphate (beta-TCP) as resorbable ceramics. Particles of these materials, ranging between about 100 microns and 300 microns in diameter, were implanted into rat tibiae, and specimens were prepared for observation at 8 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
1
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(82 citation statements)
references
References 12 publications
3
77
1
1
Order By: Relevance
“…Consequently, the function of these materials is to participate in the dynamic process of formation and reabsorption that takes place in bone tissues; so they are used like scaffolding or filling spaces allowing to the tissues their infiltration and substitution [111].…”
Section: Crystalline Bioceramic Materialsmentioning
confidence: 99%
“…Consequently, the function of these materials is to participate in the dynamic process of formation and reabsorption that takes place in bone tissues; so they are used like scaffolding or filling spaces allowing to the tissues their infiltration and substitution [111].…”
Section: Crystalline Bioceramic Materialsmentioning
confidence: 99%
“…Bioactivity of hydroxyapatite [Ca 5 (PO 4 ) 3 OH; HA] ceramics leads to a direct bonding with live bone tissue without any inclusions 1,2 but is insufficient for various applications in orthopedic and maxillofacial fields, compared with autograft bones. 3 The insufficiency requires an extraordinary accuracy of implant operation for such applications, and these restrict design of HA implant devices.…”
Section: Introductionmentioning
confidence: 99%
“…13 Neo and Kotani et al showed that b-TCP directly bonded to bone intervening no apatite layer by in vivo tests. 4,14,15 On the other hand, Daculsi et al reported formation of carbonate apatite layer in the vicinity of implanted b-TCP. 16 However, connectivity of b-TCP with host bone was reported to be strong in general and attributed to rough surface due to degradation of implanted b-TCP.…”
Section: Resultsmentioning
confidence: 99%
“…4 The b-HA layer formed on the HA surface is also regarded as one of the important factors for bonding to host bone in vivo. The b-HA formation ability enhanced by the autoclaving was expected to provide the excellent bone-bonding ability to HA and make the strong fixation with bone in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation